Pengaruh Agile Leadership Terhadap Kinerja Karyawan Melalui Pemberdayaan dan Motivasi Kerja Sebagai Variabel Mediasi: Studi pada PT Formosa Ingredient Factory Tbk (Indo-MathEdu Intellectuals Journal, 2025)
This study examines the effect of agile leadership on employee performance at PT Formosa Ingredient Factory Tbk., with employee empowerment and work motivation as mediating variables. The study uses a questionnaire survey method with a population of 84 employees. Statistical analysis is conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Agile leadership is measured through the indicators of context-setting agility, stakeholder agility, creative agility, and self-leadership agility. Employee empowerment is measured through the indicators of meaning, competence, autonomous decision-making, and impact, while work motivation is measured through recognition, achievement, responsibility, and personal growth. Employee performance as the dependent variable is measured based on work quality, work quantity, timeliness, effectiveness, and commitment. Mediation testing is conducted using the bootstrapping method because PLS-SEM does not assume a normal data distribution. The research results indicate that agile leadership has a positive and significant effect on employee performance. Employee empowerment significantly mediates the influence of agile leadership on employee performance. This means that the implementation of agile leadership will be more effective in improving performance when accompanied by enhanced empowerment. However, work motivation does not significantly mediate the relationship between agile leadership and employee performance. The influence of agile leadership on motivation and empowerment is considerable, but the effect of motivation on performance is very small.